Guidelines for the pastoral care of Poles abroad Polish - NECEL, WOJCIECH (Prawo Kanoniczne, 2017)
Wytyczne Konferencji Episkopatu Polski dotyczące Duszpasterstwa Emigracji Polskiej is a document approved at the 369th Plenary Sitting of the Conference that took place in Warsaw on 9-10June 2015. The necessity to develop Wytyczne had been recognized by Polish migration communities for a long time. Priests directly working for Poles in exile, together with Polish Council of Pastoral Care in Western Europe under the authority of the delegate of Polish Episcopal for Pastoral care of emigration, made efforts to develop general instructions for Polish-language ministry. Initiators and working committees stated that the document should take into consideration all Polish communities and their priests. Wytyczne is a document addressed to secular and monastic clergy, monks and nuns, who take care of Poles in exile’s spiritual well-being and to those who participate in taking care of Polish emigrants.